Care model for phenylketonuria (PKU) in Uruguay - Aida Lemes; Cecilia Queijo; Cristina Zabala (Instituto Nacional de Pediatría, 2014)
The Newborn screening program (PN) in Uruguay began in 1990; in 2007 the PN on filter paper was mandatory for phenylketonuria (PKU) and currently has a near 100% coverage, which ensures the detection, validation, monitoring and treatment of all patients. Many public institutions are committed to the National Newborn Screening (SNPN) but sample processing is centralized at the PN Laboratory which belongs to the Management of Social Welfare Bank Laboratories for Social Security Institute in Montevideo (BPS). From 2008 phenylalanine (Phe) quantification is perfomed in tandem mass spectrometry (MS/MS). The amount of Phe tolerance is titrated in patients with levels between 150 and 360 uml /L; above 360 uml /L treatment is started by an interdisciplinary health professional team. Phe-free formula is purchased by the BPS and provided to the patients at no cost, regardless if it is a public or private health system. The biochemical goal is to maintain Phe levels below 360 umol /L with frequent analysis of plasma Phe with a simultaneous 3 day diet diary. Phe control is performed weekly for the first six months and then every 15 days until the age of five. From 2007 to 2011, the PN has found: 7 patients with PKU, 5 persistent hyperphenylalaninemias, 3 patients with transient hyperphenylalaninemias, one patient with tetrahydrobiopterin deficiency, 8 patients were diagnosed late but had an improved behavior and attention when they were treated.